2005
DOI: 10.1115/1.1811096
|View full text |Cite
|
Sign up to set email alerts
|

Cooling the Tip of a Turbine Blade Using Pressure Side Holes—Part II: Heat Transfer Measurements

Abstract: The clearance gap between a turbine blade tip and its associated shroud allows leakage flow across the tip from the pressure side to the suction side of the blade. Understanding how this leakage flow affects heat transfer is critical in extending the durability of a blade tip, which is subjected to effects of oxidation and erosion. This paper is the second of a two-part series that discusses the augmentation of tip heat transfer coefficients as a result of blowing from film-cooling holes placed along the press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Quite a few high-pressure turbines have cooling holes on the near-tip region of the pressure side. Christophel et al [13,14] studied the cooling effectiveness, the heat-transfer coefficient, and the NHFR for this configuration. The coolant ejected from the dust holes near the leading edge of the blade tip effectively improved the thermal performance near the leading edge of the tip.…”
mentioning
confidence: 99%
“…Quite a few high-pressure turbines have cooling holes on the near-tip region of the pressure side. Christophel et al [13,14] studied the cooling effectiveness, the heat-transfer coefficient, and the NHFR for this configuration. The coolant ejected from the dust holes near the leading edge of the blade tip effectively improved the thermal performance near the leading edge of the tip.…”
mentioning
confidence: 99%
“…In the open literature [24][25][26][27], NHFR was mainly used to evaluate turbine endwall and blades cooling systems and the dimensionless temperature was set within the range of = 1.5-1.6. Since the overall effectiveness of a combustor cooling system is generally higher than the one of a turbine airfoil, more recently Facchini et al [10,11] updated this parameter to evaluate the NHFR of a cooled liner, imposing a value of = 1.2.…”
Section: Net Heat Flux Reduction and Overall Effectiveness Netmentioning
confidence: 99%
“…Kwak et al [16] further studied the effects of the positions of squealer rims, and it was found that the suction side squealer tip provided the lowest HTC on the blade tip and near tip regions compared to the other layouts. To assess the overall film-cooling benefit of the pressure side blowing, Christophel et al [17,18] measured the adiabatic effectiveness levels and the HTC.…”
Section: Introductionmentioning
confidence: 99%